Use of Natural Family Planning (NFP) and Its Effect on Couple Relationships and Sexual Satisfaction: A Multi-Country Survey of NFP Users from US and Europe - Unseld, Matthias; Rötzer, Elisabeth; Weigl, Roman; Masel, Eva K.; Manhart, Michael D. (Frontiers in Public Health, 2017)
Purpose. Birth control is a persistent global health concern. Natural family planning (NFP) comprises methods to achieve or avoid pregnancy independent of mechanical or pharmacological intervention. The Sympto-Thermal Method (STM) of NFP employs daily observation of cervical fluids and measurement of basal body temperature. This multi-country study was undertaken to describe the characteristics of STM users, understand their perceptions of NFP, and its perceived impact on relationships. Methods and Results. Questionnaires for women and men, were developed in German and translated to English, Polish, Italian, Czech, and Slovak by native speakers. 2560 respondents completed the online questionnaire (37.4% response). Participants were married (89%), well educated, and their self-perceived financial status was described as “good” or “very good” by 65% of the respondents. 47% had previously used contraceptives.95% of women and 55% of men said using NFP has helped them to know their body better. Large majorities of men (74%) and women (64%) felt NFP helped to improve their relationship while <10% felt use of NFP had harmed their relationship. Most women (53%) and men (63%) felt using NFP improved their sex life while 32% of women and 24% of men felt it was unchanged from before they used NFP. 75% of women and 73% of men said they are either “satisfied” or “very satisfied” with their frequency of sexual intercourse. Conclusions. This survey demonstrates Sympto-Thermal Method of NFP is a well-accepted approach to family planning across several Western cultures. It is consistently viewed as being beneficial to couples’ self-knowledge, their relationship, and satisfaction with frequency of sexual intercourse.